Alzheimer's Prevention Initiative: A Plan to Accelerate the Evaluation of Presymptomatic Treatments - Reiman, Eric M.; Langbaum, Jessica B.S.; Fleisher, Adam S.; Caselli, Richard J.; Chen, Kewei; Ayutyanont, Napatkamon; Quiroz, Yakeel T.; Kosik, Kenneth S.; Lopera, Francisco; Tariot, Pierre N. (Journal of Alzheimer's disease, 2011)
There is an urgent need to find effective presymptomatic Alzheimer's disease (AD) treatments that reduce the risk of AD symptoms or prevent them completely. It currently takes too many healthy people, too much money and too many years to evaluate the range of promising presymptomatic treatments using clinical endpoints. We have used brain imaging and other measurements to track some of the earliest changes associated with the predisposition to AD. We have proposed the Alzheimer's Prevention Initiative (API) to evaluate investigational amyloid-modifying treatments in healthy people who, based on their age and genetic background, are at the highest imminent risk of developing symptomatic AD using brain imaging, cerebrospinal fluid (CSF), and cognitive endpoints. In one trial, we propose to study AD-causing presenilin 1 [PS1] mutation carriers from the world's largest early-onset AD kindred in Antioquia, Colombia, close to their estimated average age at clinical onset. In another trial, we propose to study apolipoprotein E (APOE) ε4 homozygotes (and possibly heterozygotes) close to their estimated average age at clinical onset. The API has several goals: 1) to evaluate investigational AD-modifying treatments sooner than otherwise possible; 2) to determine the extent to which the treatment's brain imaging and other biomarker effects predict a clinical benefit—information needed to help qualify biomarker endpoints for use in pivotal prevention trials; 3) to provide a better test of the amyloid hypothesis than clinical trials in symptomatic patients, when these treatments may be too little too late to exert their most profound effect; 4) to establish AD prevention registries needed to support these and other presymptomatic AD trials; and 5) to give those individuals at highest imminent risk of AD symptoms access to the most promising investigational treatments in clinical trials.